Outcomes following front-line chemotherapy in peripheral T-cell lymphoma: 10-year experience at The Royal Marsden and The Christie Hospital. Issue 7 (3rd July 2018) - Gleeson, Mary; Peckitt, Clare; Cunningham, David; Gibb, Adam; Hawkes, Eliza A.; Back, Morgan; Yasar, Binnaz; Foley, Kate; Lee, Rebecca; Dash, Joanna; Johnson, Hannah; O'Hara, Catherine; et al.
Abstract: We evaluated the outcomes for patients with peripheral T-cell lymphoma (PTCL) undergoing front-line chemotherapy at our institutions between 2002 and 2012. One hundred and fifty-six patients were eligible, comprising PTCL not otherwise specified (NOS) ( n = 50, 32.0%), angioimmunoblastic T-cell lymphoma (AITL) ( n = 44, 28.2%), anaplastic large-cell lymphoma (ALCL) ALK negative ( n = 23, 14.7%), ALCL ALK positive ( n = 16, 10.3%), and other ( n = 23, 14.7%). Most patients received CHOP (66.0%) and 13.0% received an autologous hematopoietic progenitor cell transplant (HPCT). With a median follow-up of 63.4 months, 5-year overall survival (OS) and progression-free survival (PFS) was 38.8% and 19.8% respectively. Independent risk factors for inferior OS were age >60 years, International Prognostic Index (IPI) ≥ 2 and lack of complete response to induction. When responding patients were compared by receipt of an autologous HPCT versus not, HPCT was associated with improved PFS ( p = .001) and OS ( p = .046) and remained significant for PFS in multivariate analysis suggesting a possible therapeutic benefit.